Chemotherapeutic and Supportive Treatment Approaches for Cervical Cancer Patients in Indonesia: A Cross-Sectional Study - Sonlimar Mangunsong; Azzahra Nisrina; Sarmalina Simamora; Gunardi Pome; Rosnani Rosnani; Heni Sumastri (Indonesian Journal of Cancer Chemoprevention, 2025)
Cervical cancer is one of the most common cancers in women and ranks as the second leading cause of cancer-related mortality in Indonesia. Its management largely depends on the stage of disease and often requires multimodal approaches. A retrospective cross-sectional descriptive study was conducted using medical records of 185 hospitalized cervical cancer patients from January to December 2024. Data collected included age, disease stage, type of therapy, drug utilization, routes of administration, and histopathological findings. Descriptive analysis was performed and presented as frequency distributions and percentages. Most patients were aged 45–64 years (58.9%) and diagnosed at stage III (49.73%). The most common therapy was surgery (49.73%), followed by brachytherapy (20.54%) and chemotherapy (11.8%). Tranexamic acid was the most frequently prescribed drug (22.01%), while cisplatin paclitacxel and carboplatin were the primary chemotherapeutic agents. The intravenous route dominated drug administration (72.03%). Histopathology most frequently revealed medium-sized tissue lesions (3–5 cm; 21.08%). The majority of cervical cancer patients were diagnosed at advanced stages and underwent surgery as the primary treatment. Cisplatin remains the gold standard chemotherapy agent, administered primarily via the intravenous route. These findings highlight the urgent need for early detection, expanded screening, and HPV vaccination programs to reduce advanced-stage cases.Keywords: malignant carcinoma of cervix, hospitalize patient, drug utilization, histopathology.